Defying Tradition: Mr. Biswas’ Struggle Against Conventional Ideals in V.S. Naipaul’s ’A House for Mr. Biswas’ - Dr. T. Raja Sekhar (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2010)
S. Naipaul’s novel, A House for Mr Biswas, depicts the colonial context in Trinidad during World War II. Extensive analysis has been conducted on the colonial structure. The protagonist, Mr. Biswas, is portrayed as opposing conventional and conservative Hindu ideals, traditions, and ideology. He experiences a state of full isolation amidst many others, assuming the role of a solitary combatant against a formidable conservative structure permeated with antiquated fallacies, traditions, and ceremonial practices.